Time dependent dielectric breakdown in copper low-k interconnects : mechanisms and reliability models - Wong, Terence Kin Shun (2013)
The time dependent dielectric breakdown phenomenon in copper low-k damascene interconnects for ultra large-scale integration is reviewed. The loss of insulation between neighboring interconnects represents an emerging back end-of-the-line reliability issue that is not fully understood. After describing the main dielectric leakage mechanisms in low-k materials (Poole-Frenkel and Schottky emission), the major dielectric reliability models that had appeared in the literature are discussed, namely: the Lloyd model, 1/E model, thermochemical E model, E1/2 models, E2 model and the Haase model. These models can be broadly categorized into those that consider only intrinsic breakdown (Lloyd, 1/E, E and Haase) and those that take into account copper migration in low-k materials (E1/2, E2). For each model, the physical assumptions and the proposed breakdown mechanism will be discussed, together with the quantitative relationship predicting the time to breakdown and supporting experimental data. Experimental attempts on validation of dielectric reliability models using data obtained from low field stressing are briefly discussed. The phenomenon of soft breakdown, which often precedes hard breakdown in porous ultra low-k materials, is highlighted for future research.